Emotional State Evaluation of Retinitis Pigmentosa Patients with the Beck Depression Inventory - Ayşe Öner; Neslihan Sinim Kahraman; Mehmet Orkun Sevik; Kübra Kelek Tülü; Özlem Şahin; Saliha Özsoy (Türk Oftalmoloji Dergisi)
Objectives: To evaluate the incidence and severity of depression in patients with retinitis pigmentosa (RP). Materials and Methods: The Beck Depression Inventory (BDI) was administered to 74 patients with RP and 60 healthy controls. Biomicroscopic anterior segment and fundus examination, visual field, optical coherence tomography, and full-field electroretinography tests were performed in all cases. Variables were evaluated with bivariate, multiple linear, and ordinal logistic regression analyses. Results: The RP group included 40 (54%) male and 34 (46%) female patients, while the control group included 23 (38%) male and 37 (62%) female subjects. The patient group had a mean age of 39.20±12.4 years, median best corrected visual acuity (BCVA) of 0.10 decimal (1.0 logarithm of the minimum angle of resolution [logMAR]; range, 1.3-0.7 logMAR), and median visual field mean deviation (MD) score of -28.00 decibels (dB) (range, -1.00 to -34.00 dB). The median BDI score was statistically significantly higher in the patient group (19 points) than in the control group (12 points) (p<0.001). Moderate to severe depression (BDI ≥20) was detected in 61% of patients, while this rate was 25% in healthy controls. BCVA and visual field MD values were identified as predictors of depression score and severity level. The patients’ age and gender did not affect total depression score or severity. Conclusion: The prevalence and severity of depression were found to be higher in RP patients than in healthy controls. There was a significant relationship between the patient’s functional vision tests and the frequency and severity of depression. Depression reduces the reliability of visual function tests and impairs patients’ quality of life. Therefore, assessing mental health as well as functional tests is important in patients with RP.